José Maurício Nunes Garcia: a civilized mulatto in the first Brazilian Republic - Luiz Guilherme Goldberg (Per Musi, 2019)
The find of the autograph manuscript of Alberto Nepomuceno, transcription of the Festive Mass, by José Maurício Nunes Garcia, brought to light information previously unknown. Since such score was not at Alberto Nepomuceno's General Catalog (Corrêa, 1985, 1996), this identification promoted the return to the investigation of the meaning of José Maurício Nunes Garcia in the establishment of a musical identity by the First Brazilian Republic. This is the aim of this paper.